Prevalence, Risk Factors and Assessment of Depressive Symptoms in Patients With Systemic Sclerosis - Christine MARCH; Dörte HUSCHER; Emelina PREIS; Alexander MAKOWKA; Jakob HOEPPNER; Frank BUTTGEREIT; Gabriela RIEMEKASTEN; Kristina NORMAN; Elise SIEGERT (Archives of Rheumatology, 2019)
Objectives: This study aims to evaluate the prevalence of depressive symptoms among systemic sclerosis (SSc) patients using the Major Depression Inventory (MDI), identify possible risk factors, and analyze the current standard of care to raise awareness and improve clinical care for SSc patients. Patients and methods: The study included 94 SSc patients (12 males, 82 females; mean age 58.3±13.6 years; range, 28 to 83 years) who completed the MDI, Short Form 36 Health Survey, Scleroderma Health Assessment Questionnaire, Brief Fatigue Inventory and Physical Activity Questionnaire. Clinical parameters were assessed according to standardized procedures. Discharge letters were analyzed for evaluation of depressive symptoms. Results: The prevalence of depressive symptoms was 22.3%. It correlated with female sex (p=0.047), underweight (p=0.002), fatigue (p<0.001), decreased quality of life (p<0.001) and less physical activity (p=0.048). The latter three were confirmed as independent risk factors in a multivariable regression analysis. The analysis of the current standard of care revealed no assessment of depressive symptoms in the majority of patients (89.4%), including 19 with depressive symptoms according to the MDI score. Conclusion: This study confirms the high prevalence of depressive symptoms in SSc patients. There is an unmet need of regular assessment of mental health during SSc consultations. Fatigue, decreased quality of life and reduced physical activity were ascertained as independent risk factors, while special attention should also be paid to weight loss and underweight.